FELICI, Maria Serena (ed.) (2021), Glottodidatica della lingua portoghese: una prospettiva diaronica e sincronica. Bracciano: Tuga Edizioni, 205 pp. ISBN 978-88-99321-39-0 - Ramon, Micaela (Linguarum Arena, 2023)
.